(untitled) (Krakowskie Pismo Kresowe, 2021)
LVIV AND ITS INHABITANTS IN 1847-1850 IN THE LIGHT OF THE SO-CALLED “MEMOIRS” OF KSAWERA GROCHOLSKA NEE BRZOZOWSKA The purpose of this article includes reflection on the issue of how the so-called “Memoirs” of Ksawera Grocholska nee Brzozowska (1807-1872), a landowner from Podolia – elaborated by the Archbishop Zygmunt Szczęsny Feliński – show the life of the Polish aristocracy and landed class in Lviv in the first years after an event called in historiography as the Tarnów Slaughter (Galician Rabacja). Due to many reasons, it is a special biographical perspective. The text presents the figure of Countess Ksawera Grocholska nee Brzozowska, outlines the character of the source which should become a reference point for considerations included in this work. Furthermore, the most important endeavours that dominated the charitable activity of Countess Grocholska during her stay in Lviv have been described. These actions included purchase of a residential building for the needs of an orphanage being founded at the cloister of Sacré Coeur Sisters in Lviv, educational activities in favour of a finishing school for maidens, managed by this cloister, and philanthropic activity in aid of patriotic activists imprisoned in the Lviv jail, the so-called “Magdalenka”, and their families.